ASGARD+: A New Modular Platform for Bacterial Antibiotic‐Resistant Analysis. Issue 3 (9th March 2023) - Montero‐Vargas, Maripaz; Saenz‐Rojas, Alex; Suárez‐Esquivel, Marcela; Ramirez‐Carvajal, Lizbeth
Abstract: ASGARD+ (Accelerated Sequential Genome‐analysis and Antibiotic Resistance Detection) is a command‐line platform for automatic identification of antibiotic‐resistance genes in bacterial genomes, providing an easy‐to‐use interface to process big batches of sequence files from whole genome sequencing, with minimal configuration. It also provides a CPU‐optimization algorithm that reduces the processing time. This tool consists of two main protocols. The first one, ASGARD, is based on the identification and annotation of antimicrobial resistance elements directly from the short reads using different public databases. SAGA, enables the alignment, indexing, and mapping of whole‐genome samples against a reference genome for the detection and call of variants, as well as the visualization of the results through the construction of a tree of SNPs. The application of both protocols is performed using just one short command and one configuration file based on JSON syntax, which modulates each pipeline step, allowing the user to do as many interventions as needed on the different software tools that are adapted to the pipeline. The modular ASGARD+ allows researchers with little experience in bioinformatic analysis and command‐line use to quickly explore bacterial genomes in depth, optimizing analysis times and obtaining accurate results. © 2023 Wiley Periodicals LLC. Basic Protocol 1 : ASGARD+ installation Basic Protocol 2 : Configuration files general setup Basic Protocol 3 : ASGARD execution Support Protocol : Results visualization with Phandango Basic Protocol 4 : SAGA execution Alternative Protocol 1 : Container installation Alternative Protocol 2 : Run ASGARD and SAGA in container